2023
DOI: 10.3390/pharmaceutics15020651
|View full text |Cite
|
Sign up to set email alerts
|

Abigene, a Prospective, Multicentric Study of Abiraterone Acetate Pharmacogenetics in Metastatic Castration-Resistant Prostate Cancer

Abstract: Abiraterone acetate (AA) is the first-in-class of drugs belonging to the second-generation of agents inhibiting androgen neosynthesis in advanced prostate cancer. A cumulative experience attests that germinal gene polymorphisms may play a role in the prediction of anticancer agent pharmacodynamics variability. In the present prospective, multicentric study, gene polymorphisms of CYP17A1 (AA direct target) and the androgen transporter genes SLCO2B1 and SLCO1B3 (potential modulators of AA activity) were confront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The three separate parts were planned to be published independently. This pharmacogenetic study indicated that the gene polymorphism of CYP17A1 (rs743572) may be associated with the efficacy of AA treatment and may identify patients at risk for toxicity [ 6 ]. More precisely, from a multivariate analysis, the rs743572 and performance status were independently associated with significant toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The three separate parts were planned to be published independently. This pharmacogenetic study indicated that the gene polymorphism of CYP17A1 (rs743572) may be associated with the efficacy of AA treatment and may identify patients at risk for toxicity [ 6 ]. More precisely, from a multivariate analysis, the rs743572 and performance status were independently associated with significant toxicity.…”
Section: Introductionmentioning
confidence: 99%